Development of Teaching Materials for Writing Observation Report Texts Based on the Merdeka Curriculum for Class VIII MTsN 1 Jeneponto - Sahir, Sahir; Rahim, Rahman; Bahri, Aliem (FKIP - Universitas Riau, 2025)
This study aims to overcome students' low writing skills, especially in compiling observation report texts, as well as the limitations of teaching materials that are in accordance with the Merdeka Curriculum which emphasizes student-centered learning, differentiation, and strengthening the Pancasila Student Profile. The research was conducted in class VIII MTsN 1 Jeneponto with a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development process includes needs analysis, design, and preparation of contextual text-based teaching materials equipped with writing guidelines, text examples, student activities, and formative assessments. The resulting products were validated by material and media experts, then tested on a limited basis through questionnaires, interviews, and writing ability tests before and after learning. The results of the trial showed that the teaching materials were very feasible to use and had a positive impact on improving students' writing skills. Thus, this teaching material is effective in supporting the implementation of Merdeka Curriculum and can be utilized by teachers as a contextual, interesting, and meaningful learning tool.